Introduction: The Meaning and Impact of Brown Show Co. v. United States - Kenneth S. Carlston (Washington University Law Quarterly, 1963)
The judicial process is one of winnowing out undesirable from desired ideal forms of order. Each mode of action which it condemns represents an undesired distortion of an ideal form of action. It is the purpose of this introductory comment to indicate, in a series of propositions, at least some of the principal aspects of the ideal economic order which the Brown Shoe case would preserve when the issue is judicial control of the merger process under Section 7 of the Clayton Act, as amended.
Keywords: Antitrust law – Mergers